Adaptasi Sosial Lansia di Panti Jompo Kota Semarang - Adiva Fauziah Diswan; Shabrina Khoirunnisa Andar; Andhika Rizky Putra Agustina; Ajeng Ayu Hapsari; Nayla Clearista Putri Firmansyah; Az-Zahra; Citra Apik Lestari; Nabilatul Fajriyah; Siti Hikmah Anas (Jurnal Kesehatan Amanah, 2025)
This study aims to examine the social adaptation process of the elderly living in Harapan Ibu Nursing Home in Semarang City. The elderly as a late adult age group face various physical, psychological, and social changes that affect their well-being, especially when they have to live in a new environment such as a nursing home. Using a phenomenological qualitative approach, data were obtained through interviews and observations of five elderly participants who met the purposive sampling criteria. The results showed that elderly social adaptation includes three main aspects: strong and balanced affection, mature and integrated personality, and the ability to establish healthy social relationships. Most of the elderly showed good emotional coping skills through self-acceptance, gratitude, and self-control, although some of them experienced difficulties in forming meaningful social relationships. Life experiences, social environment and coping strategies were key in their adjustment process. These findings emphasize the importance of positive social support in the nursing home environment for older adults to achieve optimal psychosocial well-being.